Enhancing word recognition skills in English (FL) and Arabic (L1) through transfer effect: an intervention study - Atouf, Noureddine; Issa, Elsayed (Frontiers in Psychology, 2025)
IntroductionThe extant experimental study measured the effect of a reading training on developing word recognition skills in English (the foreign language, FL) and Arabic (the first language, L1).MethodsForty-five participants were selectively allocated to two groups: experimental (n = 25) and control (n = 20). The participants took an online lexical decision task before and after the intervention. The English measures took cognizance of frequency, regularity, and word length, while vowelization marked the Arabic stimuli. To check causality, we fitted four multilevel models to track down the improvement in accuracy and reading times (RTs) based on the interaction of fixed effects (group and time) and random effects (each individual's responses).ResultsThe English model's results revealed a statistically significant and positive interaction between the experimental group and post-accuracy rates. Post-reading times, though slightly changed, remained significant compared to the control group. The results of the Arabic models suggested a nuanced difference in the experimental group's performance.DiscussionThe findings revealed compelling insights into the adjustment of processing strategies, namely phonological and orthographic processing skills, to gain lexical access in English and Arabic. The study implicates the import of experimenting with new pedagogical approaches, i.e., reading interventions, to enhance cognitive reading skills among adult learners.